Developing Factors Of E-WOM: Intention To Buy from The Consumer Via Tik-Tok - Ratna Dewi (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
This research focuses on developing new concepts and empirically testing eWoM variable-forming factors on consumer purchasing intentions, and looking at the indirect influence of e-WOM forming indicators. This study used a sample of 100 respondents who had purchased after seeing Tik-Tok. The sampling technique used is purposive sampling by spreading questionnaires online. This study also uses the structural equation technique with data analysis using SEM-PLS. The results showed that Platform Assistance has a significant effect on purchase intention. Not only that, but the concern of others and also helping the company has a positive and significant influence on purchasing intentions. This study is still rare in looking at what factors form the variable e-whom and how these factors influence consumer purchasing intentions. This research in the design is static, a model that develops based on empirical studies and testing that is only limited to establishing a simple relationship related to e-WOM forming factors that can affect consumer purchasing intentions through a Tik-Tok application.